ETIOPATHOGENESIS, CLINICAL PRESENTATION, AND MODERN TREATMENT STRATEGIES OF PERIODONTITIS - Kurbanova Patimat,; Ganieva Aida Ismetovna,; Akhmedov Alisher Astanovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Periodontitis is a chronic inflammatory disease of the supporting tissues of the teeth that leads to progressive destruction of the periodontal ligament and alveolar bone, ultimately resulting in tooth loss if left untreated. The condition develops as a consequence of a complex interaction between pathogenic microbial biofilms and the host immune-inflammatory response, influenced by genetic, systemic, and environmental factors. Clinically, periodontitis is characterized by gingival inflammation, periodontal pocket formation, clinical attachment loss, gingival recession, and increased tooth mobility. Modern approaches to the management of periodontitis are based on early diagnosis, comprehensive risk assessment, and an individualized treatment strategy. Therapeutic measures include non-surgical periodontal therapy, surgical interventions aimed at eliminating periodontal defects, regenerative techniques, and supportive periodontal care. Timely and adequate treatment not only improves oral health outcomes but also contributes to the prevention of systemic complications associated with periodontal inflammation.